Multiple dose pharmacokinetics of quetiapine and some of its metabolites in Chinese suffering from schizophrenia - LI Kun-yan; LI Xin; CHENG Ze-neng; PENG Wen-xing; ZHANG Bi-kui; LI Huan-de (Acta Pharmacologica Sinica, 2016)
AIM: To study the multiple dose pharmacokinetics of quetiapine and its sulfoxide-, 7-hydroxy-, 7-hydroxy-N-dealkyl-metabolites in Chinese suffering from schizophrenia. METHODS: Twenty-one patients (11 females and 10 males) were given quetiapine twice daily to control the symptoms. After the dose reached 200 mg twice daily, blood were sampled to study the pharmacokinetics. The plasma concentrations of quetiapine and its metabolites were assayed by HPLC-MS. RESULTS: The main pharmacokinetic parameters of quetiapine, 7-hydroxy-N-dealkyl-quetiapine, quetiapine sulfoxide, and 7-hydroxy-quetiapine were as follows: tmax were 2.0 (0.3-5.0), 4.0 (1.5-6.0), 3.0 (0.5-5.0), and 3.0 (0.5-5.0) h respectively; t1/2 were (7+/-3), (9.4+/-2.7), (7+/-3), and (8+/-5) h, respectively; Cmax(SS) were (678+/-325), (19+/-5), (451+/-216), and (58+/-22) microg/L, respectively; Cmin(SS) were (51+/-68), (3.3+/-1.6), (35+/-36), and (5+/-4) microg/L, respectively; Cav(SS) were (295+/-144), (13+/-4), (209+/-71), and (28+/-9) micro/L, respectively; AUC(0-12)(SS) were (3,538+/-1 728), (153+/-44), (2,512+/-854), and (335+/-104) microg.h.L(-1), respectively; AUC(0-infinite)(SS) were (5,534+/-4 198), (287+/-107), (3,858+/-2 012), and (529+/-262) microg.h.L(-1), respectively; Ke were (0.11+/-0.03), (0.079+/-0.019), (0.11+/-0.03), and (0.103+/-0.028) h(-1), respectively; CL/F and V/F of quetiapine were (67+/-25) L.h(-1) and (672+/-394) L, respectively. The plasma concentrations for the four compounds reached a steady state within 48 h at the dose of 200 mg initiation. These parameters were not statistically different between genders. CONCLUSIONS: Quetiapine was absorbed quickly, distributed widely, and metabolized mainly to be quetiapine sulfoxide. The elimination speeds of quetiapine and its three metabolites were similar. Gender had no effect on the pharmacokinetics of quetiapine and its metabolites. The clinical dosage regime caused no drug accumulation.